Church History (Cambridge)
This quarterly peer-reviewed journal publishes original research articles and book reviews covering all areas of the history of Christianity and its cultural contexts in all places and times, including its non-Western expressions. Specialists and historians of Christianity in general find Church History: Studies in Christianity and Culture an international publication regularly cited throughout the world and an invaluable resource.
Keywords: Church History